Rozważania nad istotą demokracji w polskich naukach polityczno-prawnych w okresie międzywojennym : Wprowadzenie - Wojtacki, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The aim of the article is to present reflections on the democracy in the Second Polish Republic, particularly in scientific and political discourse. In order to accomplish this objective, an overview of definitions represented by the most important pre-war researchers of state law as well as active politicians is provided. Also, the basic sources of definitional deliberations and the influence of Western European philosophy on the development of studies of political doctrines in Poland in the interwar period are depicted. The base of reference sources was constituted by encyclopaedias, textbooks, and political press, for the collation of which historical and legal methods (the textual analysis and comparative one) were used. In consequence of the conducted examination, the main directions of redefinition of democracy as a political system were delineated, primarily towards organized democracy which is identified with authoritarian form of government and pure adjectiveless democracy.
Keywords: autorytaryzm; demokracja; doktryny polityczne; myśl polityczna; II Rzeczpospolita